The Effects of Smoking on Extensor Mechanism Injury and Post Surgical Complications: A National Database Study. Issue 7 (31st July 2020) - Yang, Daniel; Curtis, Kyle; Daniels, Alan; Owens, Brett; DeFroda, Steven
Objectives: The extensor mechanism of the knee is composed of the quadriceps tendon, the patellar tendon, and the patella. These injuries are associated with several comorbidities including diabetes mellitus, rheumatoid arthritis, gout, hyperparathyroidism, chronic renal failure and corticosteroid or anabolic steroid use. Cigarette smoking is also a known risk factor for extensor mechanism rupture, with increased number of pack years associated with decreased tendon thickness and increased incidence of rupture. Smoking has also been shown to have deleterious effects on tendon repair, with a higher frequency of post-surgical complications involving soft-tissue infection, failure of wound healing, and worse functional outcomes in smokers relative to non-smokers. Using a large national data set of extensor mechanism repair patients, risk factors for extensor tendon injury, and the effects of smoking on the risk of postoperative complication were analyzed. We hypothesized that patients who smoke would have higher rates of post-surgical complications relative to non-smokers. Methods: This retrospective study utilized the Humana insurance data set within the PearlDiver Patient Records Database (PearlDiver Inc, Fort Wayne, Indiana), a large private/commercial and Medicare medical record database. Patients who underwent extensor mechanism repair using Current Procedural Terminology (CPT) codes CPT-27380, CPT-27524, and CPT-27385 were identified. These patients were partitioned into two cohorts, one coding for tobacco use or nicotine dependence before their repair and another who did not. Gender, age, obesity, morbid obesity, diabetes, hypertension, chronic obstructive pulmonary disease (COPD), steroid use, renal dialysis, thyroid disease, end stage renal disease, hyperlipidemia, and systemic inflammation rates were assessed in each population. Postoperative complications, including 30-day readmission rate, 1-year revision rate (defined as a repeat procedure within 1 year post-index surgery), urinary tract infection (UTI), surgical site complication, deep vein thrombosis (DVT), sepsis, pneumonia, myocardial complications, respiratory complications, cardiac complications, cardiac arrest, coagulation, and death were investigated for the two groups. Multivariate logistic regression was used to calculate odds ratios, controlling for age, gender, race, Charlson Comorbidity Index (CCI), and all risk factors that were found to have significantly different risks between smoking and non-smoking patients. Statistical analysis was performed using the PearlDiver software, which runs R, Version 1.1.442. An α value of .05 was set as the level of significance. Results: Among extensor mechanism repair patients, 1559 (22.5%) smoking patients and 5376 (77.5%) non-smoking patients were included in the analysis. The age distribution of both cohorts of patients was similar, with most patients being between 65 and 74 years of age (Table 1). Pre-operative comorbidities associated with extensor mechanism injury were found to be significantly different between the smoking and non-smoking cohorts, specifically with regards to smokers 11.2% vs. 5.9% (p<0.0001) were obese, 51.4% vs. 37.1% had diabetes (p<0.0001), 82.5% vs. 34.1% were hypertensive (p<0.0001) and 10.3% vs. 1.9% had COPD (p<0.0001) at the time of initial injury. Smoking extensor mechanism repair patients had higher rates of 1-year revision, total 30-day complications, UTI, surgical site complications, sepsis, pneumonia, myocardial complications, and respiratory complications (Table 2). Conclusions: Patients who are smokers at the time of extensor mechanism injury are more likely to have a higher number of medical comorbidities including obesity, diabetes mellitus, hypertension, and COPD. Recognizing that smokers with extensor mechanism injuries have more medical comorbidities at baseline, placing them at higher risk for anesthesia, should influence the surgeons' decision making with regards to location of the surgery (hospital versus ambulatory surgery center), as well as the possible need for post operative admission Additionally smoking portends a much higher complication rate following extensor mechanism repair, most notably in our study, a 65.7% incidence of need for 1-year revision, and a 21.4% incidence of a 30-day complication. It is important for surgeons to recognize the increased risk of complications in these patients and counsel them regarding these risks and encourage smoking cessation. Table 1. Demographic Characteristics of Smoking and Nonsmoking Patients of Extensor Mechanism Repair Extensor Mechanism Repair Smoking Nonsmoking Variable n % n % All Patients 1559 5376 Age Group  <10 0 0.0 0 0.0  10 to 14 0 0.0 51 0.9  15 to 19 0 0.0 119 2.2  20 to 24 0 0.0 77 1.4  25 to 29 13 0.8 69 1.3  30 to 34 24 1.5 104 1.9  35 to 39 37 2.4 140 2.6  40 to 44 41 2.6 180 3.3  45 to 49 82 5.3 195 3.6  50 to 54 136 8.7 293 5.5  55 to 59 200 12.8 339 6.3  60 to 64 236 15.1 444 8.3  65 to 69 454 29.1 929 17.3  70 to 74 447 28.7 929 17.3  75 to 79 292 18.7 729 13.6  80 to 84 147 9.4 466 8.7  85 to 89 49 3.1 158 2.9  90 and over 16 1.0 189 3.5 Year  2007 155 9.9 279 0.1  2008 209 13.4 357 0.1  2009 262 16.8 367 0.1  2010 298 19.1 404 0.1  2011 331 21.2 477 0.1  2012 391 25.1 479 0.1  2013 483 31.0 595 0.1  2014 565 36.2 708 0.1  2015 498 31.9 905 0.2  2016 265 17.0 743 0.1  2017 51 3.3 163 0.0 Gender  Female 824 52.9 2958 55.0  Male 736 47.2 2418 45.0 Table 2. Complications following Extensor Mechanism Repair: Smoking vs Nonsmoking Patients Nonsmoking Smoking Male Gender Complications n % n % aOR 95%CI p-value aOR p-value 30dy Readmission 1470 27.7 481 30.9 1.03 0.89 1.19 0.6902 0.67 <0.0001 1yr Revision 363 6.8 1023 65.7 2.74 2.33 3.24 <0.0001 1.02 0.7781 Total Complications 450 8.5 334 21.4 2.25 1.90 2.68 <0.0001 1.22 0.0184 UTI 262 4.9 179 11.5 2.23 1.78 2.79 <0.0001 4.76 <0.0001 Site 174 3.3 149 9.6 2.49 1.93 3.20 <0.0001 1.02 0.8623 DVT 158 3.0 74 4.7 1.33 1.11 1.80 0.0739 1.63 0.0006 Sepsis 59 1.1 62 4.0 2.56 1.70 3.85 <0.0001 1.20 0.3576 Pneumonia 17 0.3 38 2.4 5.22 2.73 10.33 <0.0001 0.87 0.6306 Myocardial 28 0.5 50 3.2 4.36 2.62 7.37 <0.0001 1.05 0.8299 Respiratory 94 1.8 96 6.2 2.27 1.63 2.78 <0.0001 1.08 0.6220 *Multivariate logistic regressions adjusted for gender, age, race, CCI, and all risk factors that showed significant in the prior analysis.